NSCAs Performance Training Journal - Nutrition (NSCAs Performance Training Journal, 2011)
Effects of Antioxidants on Sports Performance - Andrew Vu: This article examines antioxidants and their effects on the human body, specifically during sports performance, and provides recommendations for improving various deficiencies.